(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
This article introduces the historical and contemporary context of dual language early education in Hungary and links this context to both current early childhood teacher training programs in Sopron, Hungary, and the author’s initial and informal observations in two types of language focused preschool classrooms. Results of these observations offer preliminary information that will be used to inform future research.